The Dilemma Between Ethics and Creativity: The Problem of Authenticity in the Productions of Gus Baha’s Preaching Content on YouTube - Najib, Abdul (Mediakita, 2025)
This research aims to discuss the creative and ethical issues that arise from using Gus Baha's digital assets to produce religious content. This article focused on the two channels: ‘Santri Gayeng’, which requested permission from Gus Baha for content production, and ‘Pengajian Gus Baha’, an anonymous channel. This research employed the netnography method to collect data by observing the preaching content on the two channels and conducting interviews with the channel owners. This article finds three conclusions. First, Santri Gayeng and Pengajian Gus Baha' are identified as religious digital creative agencies (RDCAs), which are individuals or groups with the ability to manage digital media to provide and strengthen traditional authority. This concept differs from that of religious digital creatives (RDCs), who utilize their creative management of digital media to establish authority for themselves. Second, both RDCAs have their own standards of morality, so they both deserve to be called moralists, even though they utilize digital assets from others. Third, the moral values of both RDCAs enable them to drive creativity, allowing these agencies to produce engaging content and garner significant social media interaction.